PERANCANGAN SIGN SYSTEM PASAR RAYA BLOK III KOTA PADANG - Putri Ramadani, Ir. Drs. Heldi, M.Si., Ph,.D., Drs. Yusron Wikarya, M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The development of the Pasar raya market as a convenient and modern trade facility has become a shopping necessity for the people of Padang. But it has not been supported by adequate information infrastructure, and the optimal sign system in the Padang Block III Pasar Raya, so that it is feared that it will confuse visitors. The purpose of designing the Padang Block III Pasar Raya sign system can guide and provide information, directions will a place for traders and visitors in the market block III city of Padang, which consists of the Identification Sign, Direction Sign and Information Sign. The design method is 4-D (Four-D Models). with the analysis approach is 5W + 1H (what, who, where, when, why and how) to find the solution for the problems. This design produces three sign systems as the main media Identification Sign, Direction Sign and Information Sign, and the support media that is used to support the main media are stickers, posters, banners, infographics and outdoor mapping, as supporting main media and as promotional media.Keywords: Sign System, Informative, Communicative, Effective, Pasar Raya.